Ageing effect of lower limb muscle activity for correlating healthy and osteoarthritic knees by surface electromyogram analysis - Md. Moznuzzaman; Tawhidul Islam Khan; Budrun Neher; Kenbu Teramoto; Shuya Ide (Sensing and Bio-Sensing Research, 2022)
The ubiquity of osteoarthritis (OA) in human knees has been intensified among the ageing society of the world. The intention of this work is to assess the impact of the ageing on lower limb muscles associated with OA knees through sit-stand-sit movements. Out of total eighty-four participants, 51 healthy and 33 OA patients participated in the research. Surface EMG technique was used to investigate the activities of the vastus lateralis (VL), rectus femoris (RF), vastus medialis (VM), and the medial head of the gastrocnemius (MHGM) with the increase of age. Healthy participants were classified into three groups based on their age. Jarque-Bera normality test and independent t-test were performed for statistical clarifications. Muscle activities of the middle age and older people were found noticeably higher and lower compare to that of the young and OA group respectively. The quadricep muscles were found to contribute more than the calf muscle.